Food insecurity and insufficiency at low levels of food expenditures - Craig Gundersen; David C. Ribar (Institute for the Study of Labor (IZA), 2005)
This study uses data from the December 2003 Food Security Supplement of the CPS to compare the food insufficiency and insecurity measures with objective measures of food expenditures and objective and subjective measures of food needs. The study examines the general relationships between these variables and finds that reports of food hardships are positively associated with food expenditures and negatively associated with needs. The study goes on to examine reports of food hardships at low very levels of food expenditures, where we conjecture that most people should experience food problems. When expenditures are scaled by an objective measure of needs, there is no point along the expenditure distribution where more than half of the survey respondents report experiencing being food insufficient or insecure. However, when expenditures are scaled by a subjective threshold, we observe near-universal reporting of food problems at low levels of expenditures. The findings indicate that the food insufficiency and insecurity measures each incorporate a large subjective component, which limits the usefulness of the measures for comparing the extent of food hardships across populations or over time or evaluating the effects of assistance programs.
Keywords: I3; 330; food insecurity; food insufficiency; expenditures; non-parametric regression